2008
DOI: 10.1182/blood-2007-02-074849
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic polymorphisms associated with risk for pulmonary hypertension in sickle cell disease

Abstract: Up to 30% of adult patients with sickle cell disease (SCD) will develop pulmonary hypertension (pHTN), a complication associated with significant morbidity and mortality. To identify genetic factors that contribute to risk for pHTN in SCD, we performed association analysis with 297 single nucleotide polymorphisms (SNPs) in 49 candidate genes in patients with sickle cell anemia (Hb SS) who had been screened for pHTN by echocardiography (n = 111). Evidence of association was primarily identified for genes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 28 publications
2
47
0
1
Order By: Relevance
“…5,6 Several retrospective studies have identified specific single nucleotide polymorphisms (SNPs) associated with stroke in pediatric patients with SCA, using candidate gene approaches. [7][8][9][10][11][12][13][14] However, the majority of these potential modifiers did not have a replicated association with stroke using independent validation cohorts. 15 Only a few genetic modifiers have confirmed association with stroke, such as a-thalassemia trait being protective against stroke, but these do not explain the entire genetic contribution to stroke risk.…”
Section: Introductionmentioning
confidence: 96%
“…5,6 Several retrospective studies have identified specific single nucleotide polymorphisms (SNPs) associated with stroke in pediatric patients with SCA, using candidate gene approaches. [7][8][9][10][11][12][13][14] However, the majority of these potential modifiers did not have a replicated association with stroke using independent validation cohorts. 15 Only a few genetic modifiers have confirmed association with stroke, such as a-thalassemia trait being protective against stroke, but these do not explain the entire genetic contribution to stroke risk.…”
Section: Introductionmentioning
confidence: 96%
“…Both conditions are associated with elevated plasma level of asymmetric dimethylarginine, an endogenous inhibitor of nitric oxide (NO) synthase [34,35]. Genomics analyses have shown an association in both conditions with genetic polymorphisms in the BMP6, TGFBR3 and Klotho genes, important in vascular biology, including regulation of NO production [29,36]. There has been evidence of severely impaired red cell deformability, increased density and altered rheology [22,33,37].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Ashley-Koch and colleagues recently published evidence that genetic polymorphisms identified in the TGβ superfamily are associated with PH risk in SCD, including activin A receptor, type II-like 1 (ACVRL1) and bone morphogenic protein receptor 2 (BMPR2), single nucleotide polymorphisms found to also be associated with primary PH. 66 Priapism and cutaneous leg ulcers have been reported in patients with thalassemia intermedia and other hemolytic anemias in addition to SCD. 52 In a recurring theme, this complication was found to be most prevalent in patients with SCD with the highest rates of hemolysis, 7,67 and reported by Nolan and colleagues to be associated with a genetic polymorphism in Klotho, a gene that regulates NO bioavailability.…”
Section: Vascular Phenotypes Of Sickle Cell Diseasementioning
confidence: 99%